Diagnosis of the urban design of the city of Huánuco - Aréstegui Matutti, Darcy E. (2009)
The research work was carried out with the aim of diagnosing the urban situation of the city of Huánuco, in order to determine the sustaining of the Professional Academic School of architecture at Hermilio Valdizán Public University. It was designed a study of type applied in the descriptive level; analyses were carried out on the architectural conditions of the city of Huánuco, through opinions of the social actors involved in topics of formulation of political public and citizens common of a sample formed of 149 persons, so then the bibliographical material in reference also was analyzed. The techniques used for gathering data were: the survey was formulated according to the scale of Likert; it was carried out interviews and analyze to the lists of collation and the obtained results were: 85% of the population from Huánuco, consider that in spite of existing a Master Plan, nevertheless, this one has not been operative since it has not allowed to control the disorderly Urban growth, as far as the Road System; Uses of the ground and Urban Equipment, it also was found that 95% of the premises destined, for uses public, do not count on an infrastructure that are adapted to the norms of accessibility for disabled people, 85% of the people think that it is necessary the intervention and participation of professionals in architecture in the elaboration of projects and Management of Urban Development, linked to the construction of all kind of works. It was concludes that the necessity exists to train professionals in the field of the architecture and Urbanism, in order that these professionals contribute to the urban development, social and integral of the Region.